Hubungan antara Kadar Soluble CD4O Ligand (sCD4OL) dengan Kejadian Sindroma Koroner Akut (SKA) - Jusak Nugraha; Myrza Elita; M. Aminuddin (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2018)
Introduction: Acute coronary syndrome (ACS) is manifestation of coronary heart disease (CHD), which is the leading cause of death in Indonesia. CD40 ligand (CD40L) stored in alpha granule of platelet will be translocated immediately to the surface when plaletet is active, and then released from the surface as soluble CD40 ligand (sCD40L). Soluble CD40 ligand (sCD40L) has role in connecting the inflammatory process, atherosclerosis, and thrombosis. The aim of this study is to study correlation between sCD40L level and ACS in patients with chest pain. Methods: Subject of this study was 40 patients with chest pain that came to emergency ward of RSUD dr. Soetomo Surabaya. Patients were divided into two groups based on the diagnosis ACS and non ACS, which was established with electrocardiography(ECG) and Troponin-T level. Patients’sera were examined sCD40L level using enzyme-linked immunosorbent assay (ELISA) kit from Quantikine®. Results: Twenty six (65%) were diagnosed as ACS, and 14 (35%) were non ACS. ACS diagnosis consists of ST-segmen elevation myocardial infarction (STEMI), non-ST-segmen elevation myocardial infarction (NSTEMI), and unstable angina (UA), with the highest proportion was STEMI in 15 (57%). The mean of sCD40L level in ACS patients (5.45 ± 3.70 ng/mL) was significantly higher compared with non ACS patients (1.97 ± 1.33 ng/mL) (p